UPAYA INDONESIA DALAM MENGATASI PERMASALAHAN PENYELUNDUPAN MANUSIA (PEOPLE SMUGGLING) DI KEPULAUAN RIAU PADA TAHUN 2009-2012 - M. Irsyadtul Ali; Yuli Fachri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research explains how Indonesia's efforts to solve the problem of people smuggling in Riau Islands, Indonesia (2009-2012). Indonesia, which is an archipelagic country, has border areas by sea, land and air facing directly with neighbour countries, one of them is Riau Islands region. Under these situation, Indonesia becomes a country with the highly vulnerable to the crime of people smuggling because of the weakness of guarding the border areas.The author collects data from books, encyclopedias, journals, mass media and internet websites to analyze Indonesia's efforts to solve the problem of people smuggling in Riau Islands (2009-2012). The theory used in this research is the perspective of realism with the theory of Public Policy by James E. Anderson.The results show that Indonesia has done various ways to prevent the occurrence of people smuggling cases by ratifying the palermo convention with the 2 protocols to prevent the problem of people smuggling and illegal immigrants into the country and also work together with neighbour countries to exchange information. The law used to give effect to the perpetrators of people smuggling is using UU no.6 of 2011 on immigration and for illegal immigrants smuggling victims submitted to UNHCR and IOM.Key words: People smuggling, illegal immigrants, public policy, convention, protocol